Perdebatan Teori Transisi Demokrasi - Alkatiri, Zeffry (UI Scholars Hub, 2007)
This paper discusses the debate on the theories of democratic transition that has been going on since the 1960s. Democratic thoughts area always related to a context of change in a society. The theories of democratic transition had come to be debated again when the communist block countries and Russia changed their ideology and entered a democratic transition process. This debate provide a reference point and comparative framework that can be employed to evaluate socio-political changes in other countries that are experiencing similar democratic transition process and all of the consequences and challenges it poses.